Modern Russian and Foreign Approaches to Strategic Planning of the Regional Socio-Economic Development - PRUDSKIY, Vladimir Grigorievich; DEMIN, Grigoriy Alekseevich; OSHCHEPKOV, Andrei Mihailovich; GERSHANOK, Aleksandr Aleksandrovich (Journal of Advanced Research in Law and Economics; Vol 8 No 2 (2017): Volume VII, Issue 2(24), Spring 2017, 2017)
The article is devoted to the review of Russian and foreign approaches to strategic planning of the regional socio-economic development. The article applies a systematic approach as a basic one where the strategies for socio-economic development of regions are based on the relevant projections of regional economic development and the concepts of appropriate regional economic policy. This forms the theoretical and methodological foundation for various modern Russian and foreign approaches to strategic planning of the regional socio-economic development. The article discusses two key domestic approach to strategic planning of socio-economic development of the region – corporate and territorial, as well as five foreign approaches. The article also presents the results of the comparative analysis of the existing approaches to strategic planning of socio-economic development of the region.